Pergularia tomentosa, from Traditional Uses to Ecology and Phytochemistry - SH Hosseini Kahnouj; M Ayyari; Hossein Azarnivand; S Piacente; MA Zare Chahouki (Institue of Medicinal Plants, ACECR, 2017)
Background: Pergularia tomentosa L. has several traditional uses and biological activities which need to be more investigated. Objective: In this study, some ecological and phytochemical properties of Pergularia tomentosa were assessed. The flavonoids and cardenolides in the aqueous extract of leaves were identified with LCMS techniques. Methods: Some quantity characteristics of P. tomentosa were measured. Extraction was performed according to the traditional method (aqueous extract at room temperature). Metabolite profiling was conducted using untargeted liquid chromatography coupled to high resolution mass spectrometry (LCeESI-OrbitrapeMS). Data were analyzed by Xcalibur version 2.1. Results: Results showed that length of roots, leaves and fruits and the height of aerial parts were 23-30 cm, 2.5-3.2 cm, 4.9- 5.4 cm and 40-58.00 cm, respectively. Physiography and canopy cover were two important variables on these properties. We also identified 19 natural products in aqueous extract, 15 phenolics and flavonoids and 4 cardenolides. Three flavonoids (8, 11 and 14) and one cardenolide (17) had been previously isolated in P. tomentosa and 3 cardenolides (5, 18 and 19) has been reported for the first time in this plant. Conclusion: Results indicated that the leaves of P. tomentosa are a rich source of flavonoids and cardenolides. These findings suggest that leaves of this plant can be a good source of natural antioxidant and antitumor compounds. However, this plant needs special conservational efforts. Therefore, planting this plant under the canopy or along the borders of waterways can help in an appropriate habitat for its conservation and reclamation.